Evaluation of Physico-Chemical Parameters of Pouch Milk Samples Available In Butwal - Shrestha, Deepak Kumar (Butwal Campus Journal, 2020)
In the present study four different brands of pouch milk samples viz, DDC, Lumbini, Godhuli and Panchamrit commercially available in Butwal city were collected and the physicochemical characteristics including- moisture, pH, casein and fat were analyzed. It was found that all measured parameters were found as per recommended standard as compared with reported nutritional quality of milk from various countries. The main objective of the study is to determine some of the physico-chemical properties of milk sample and to provide nutritional benefits for health. All these tests were carried out in Chemistry laboratories of BMC and DDC in ButwaI industrial Area. The value of pH ranged from 6.69 to 6.72, moisture ranged from 90.5% to 91.45%,the casein ranged from 3.12 to 3.4 and fat ranged from 2.87% to 3.06%, where Lumbini pouch milk had highest pH while Godhuli had highest moisture content and casein also while Lumbini had highest fat content. These parameters were determined and data were analyzed from period of15 March 2019 to 30 May 2019.